Modeling atmospheric vegetation uptake of PBDEs and PAHs using field measurements - St-Amand, Annick D (University of Ottawa (Canada), 2008)
This thesis examines the accumulation of polybrominated diphenyl ethers (PBDEs) and polycyclic aromatic hydrocarbons (PAHs) in vegetation in order to develop an interpretative scheme to determine deposition velocities of semi-volatile organic compounds (SVOCs) onto vegetation. PBDEs are flame retardants used in a variety of consumables. Although relatively non-volatile, these compounds have been quantified around the world extending to otherwise pristine ecosystems providing empirical evidence for their long-range transport. However, modeling studies indicate that their long-range atmospheric transport (LRAT) potential is at best moderate. However, recent modeling studies have suggested that vegetation may play an important role in their global distribution. PAHs are also ubiquitous contaminants. These can be released through both natural and anthropogenic sources. Some are considered highly carcinogenic and their potential impact on human health may be due to their association to particulates. Although their environmental fate is perhaps better understood, the processes involved in surface-air exchange, particularly with vegetation, have not been well documented. Spruce needles and atmospheric (gaseous and particulate-bound) PBDE and PAH concentrations were monitored bi-weekly from February 2004 to June 2005 to examine potential weather-related and seasonal effects. An efficient extraction method for PBDEs from spruce needles was developed. Finally, using measured concentrations, surface-air exchange was considered and a modeling concept was developed to determine deposition velocities to vegetation. Following their emergence, spruce needle PBDE and PAH concentrations increase gradually over time although decreasing briefly following snowmelt with a minimum coinciding with the following year's bud burst. Atmospheric concentrations of PBDE and PAH, both gaseous and particulate-bound, were linked to daily weather events. PBDE gaseous concentrations increased with temperature, whereas PAH concentrations were generally highest in the winter, likely reflecting increased emission. Analysis of air mass back trajectories and local wind directions revealed that particulate-bound PBDEs, along with both gaseous and particulate-bound PAHs originated from local sources, whereas gaseous PBDEs were likely from distant sources. Using measured atmospheric PBDE and PAH concentrations, particulate-gas partitioning was examined. Particulate-gas distributions correlated significantly with log KOA values and a significant temperature dependence was observed for most compounds considered, except the higher PBDE congeners. From compounds exclusively associated to particulates, the particulate-bound deposition velocities were calculated at 3.8 and 10.8 m/h for PBDEs and PAHs, respectively. The different vP values obtained for PBDEs and PAHs may indicate association with different particulates. Net gaseous transfer velocities correlated significantly with log KOA values and ranged from 2.4 to 62.2 m/h for PBDEs and from negligible to 75.6 m/h for PAHs. These derived values were then used to monitor PBDE and PAH accumulation in vegetation through time, and these agreed well with measured values. This study provides the necessary background for modeling PBDE and PAH transport between air and coniferous vegetation globally.
Keywords: Biogeochemistry.; Biology, Plant Physiology.